[PP.01.06] AMINO ACIDS KYNURENINE AND QUINOLINIC ACID AND TARGET ORGAN DAMAGE IN HYPERTENSIVE PATIENTS – NOVEL INSIGHTS FROM THE STYRIAN HYPERTENSION STUDY. (September 2017) - Verheyen, N.; Gaksch, M.; Meinitzer, A.; Grübler, M.; Trummer, C.; Schwetz, V.; Pandis, M.; Ablasser, K.; Kolesnik, E.; Von Lewinski, D.; Brussee, H.; März, W.; et al.
Abstract : Objective: Experimental studies indicated a contribution of the essential amino acids kynurenine and quinolinic acid to cardiovascular disease. We therefore investigated the associations between their serum concentrations and surrogates of hypertensive target organ damage in a cohort of hypertensive patients. Design and method: Cross-sectional data from 514 hypertensive participants of the Styrian Hypertension Study were analyzed who had been enrolled at a single tertiary care hospital. Serum concentrations of kynurenine and quinolinic acid were correlated with N-terminal pro-brain B-type natriuretic peptide (NT-proBNP) and 24-hours urinary protein-to-creatinine-ratio (PCR) in multivariate linear regression analyses. Results: Mean age was 61.2 +/− 10.5 years (52.5% females) and mean 24-hours ambulatory blood pressure was 127.5/76.4 +/− 13.8/9.5 mmHg. Medians and interquartile ranges of NT-proBNP and PCR were 82 (42–152) pg/ml and 67.5 (52–93.4) mg/mmol creatinine, respectively. Both kynurenine and quinolinic acid were significanty related with NT-proBNP and PCR in univariate analyses. After adjustment for age, sex, systolic nighttime blood pressure, estimated glomerular filtration rate, body mass index, C-reactive protein, concomitant blood pressure and heart failure medication and other traditional cardiovascular risk factors, quinolinic acid was significantly related with NT-proBNP (adjusted beta-coefficient = 0.133, P = 0.003) and PCR (beta = 0.216, P < 0.001), while kynurenine was not. Restricting these analyses to patients with NT-proBNP > 125 pg/ml (n = 171), both amino acids were independently related with NT-proBNP (quinolinic acid: beta = 0.249, P = 0.027; kynurenine: beta = 0.207, P = 0.027). Conclusions: Serum concentrations of quinolinic acid and, to a less extent, kynurenine determine hypertensive target organ damage independently of potentially confounding factors. These clinical data extend previous experimental studies indicating that quinolinic acid and kynurenine may mediate target organ damage in patients with arterial hypertension.